The Antinociceptive and Anti-Inflammatory Activities of Aspidosperma tomentosum (Apocynaceae) - Anansa Bezerra de Aquino; Luiz Henrique Agra Cavalcante-Silva; Carolina Barbosa Brito da Matta; Willians Antônio do Nascimento Epifânio; Pedro Gregório Vieira Aquino; Antônio Euzébio Goulart Santana; Magna Suzana Alexandre-Moreira; João Xavier de Araújo-Júnior (The Scientific World Journal)
We investigated the antinociceptive and anti-inflammatory activities of the crude ethanolic extract (CEE), its fractions, and the flavonoid isorhamnetin from Aspidosperma tomentosum using models of nociception and inflammation in mice. In the writhing test, the CEE and its fractions (except for soluble phase, CHCl3 100% and EtAcO 100%) at 100 mg/kg p.o. induced antinociceptive activity. Isorhamnetin (100 μmol/kg, p.o.) was also active. In the hot plate test, only the treatment with the fractions Hex : CHCl3 50%, CHCl3 100%, and CHCl3 : MeOH 5% (100 mg/kg, p.o.) increased the latency time, reversed by the opioid antagonist naloxone. Fractions that were active in the hot plate test did not show catalepsy condition. It was observed that CEE, all fractions, and isorhamnetin reduced the formalin effects in the neurogenic phase. In the inflammatory phase, only CEE, isorhamnetin, and CHCl3 100% and CHCl3 : MeOH 5% fractions were active. CEE and all fractions, except for CHCl3 : MeOH 10% fraction, isorhamnetin, and soluble fraction were able to produce an antioedematogenic activity in the ear capsaicin-induced edema test. In the thioglycolate-induced peritonitis, only EtAcO 100% fraction was not active. The results demonstrate that A. tomentosum has antinociceptive and anti-inflammatory activities in animal models.